Maternal Anxiety and Sleep Quality Affects of Neonatal Brain-Derived Neurotrophic Factor - Amel Yanis; Rahmi Andrita Yuda; Hudila Rifa Karmia (Jurnal Kesehatan Masyarakat, 2023)
Anxiety conditions and sleep disorders in pregnant women will affect theBrain-Derived Neurotrophic Factor (BDNF) level of the baby's umbilical cord blood, which will then affect the growth and development of the baby. This study aims to assess the relationship between maternal anxiety and sleep quality with neonates' BDNF levels. The research design was a cross-sectional study. Pregnant Women who gave birth by cesarean delivery method with a gestational age of ≥ 37 weeks, Totally 78 pregnant women were recruited. Anxiety levels and sleep quality were assessed by questionnaire, and BDNF levels were taken from the umbilical cord blood and then checked using the ELISA method. Data were analyzed by One-Way-Anova and Independent T-test. There was a significant association between anxiety levels and sleep quality with Neonatal BDNF levels (p = 0.000). The results obtained for pregnant women without anxiety, the mean level of BDNF is 2.017 ± 0.138 ng /ml, mild anxiety the mean value of BDNF level is 1.792 ±0.134 ng/ml, moderate anxiety the mean value of BDNF level is 1.708±0.177 ng/ ml, severe anxiety the mean value of BDNF levels was 1.585±0.257 ng/ml . Pregnant women with good sleep quality had the mean BDNF level of 1.969±0.211 ng/ml, while the mean BDNF level of poor sleep quality was 1.673 ±0.188 ng/ml. Conclusion: The higher the anxiety level of pregnant women, the lower the average Neonatal BDNF level is. The worse the sleep quality of pregnant women, the lower the average Neonatal BDNF level is.